How to investigate damp : practical site inspection skills and remedial options - Burkinshaw, Ralph (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The aim of this book is to take the reader by the hand and show them exactly how to carry out various inspection techniques to identify the causes of damp in buildings"--
OCLC-licensed vendor bibliographic record.
Keywords: Dampness in buildings; Building inspection; ARCHITECTURE / Reference; TECHNOLOGY / Construction / General; TECHNOLOGY / Construction / Plumbing